Modelling of light weight floor/ceiling structures - Chung, H (The Australian Acoustical Society. The New Zealand Acoustical Society., 2006)
This talk presents a mathematical model of light weight timber floor/ceiling structures. The structures studied here consist of three basic components, upper plate, joist beams and ceiling. The shape of the whole structure is rectangular with the edges simply supported. Connections between the joist beams, the upper plate and the ceiling are considered. This connection conditions include the slippage and the springs. The configuration of the structure is made pro-gressively more complex by adding more components such as cavity air and stiffening battens.